Riboregulation in Pseudomonas aeruginosa - Silistre, Hazel (2016)
The opportunistic human pathogen Pseudomonas aeruginosa controls virulence, production of secondary metabolites, motility, biofilm formation, growth in anaerobic conditions, intracellular and intercellular signalling and the switch from an acute to a chronic mode of infection at the transcriptional and post-transcriptional levels by modulation of the Gac/Rsm system. Cell density-dependent signal accumulation and environmental stimulators such as pH changes and ion limitation activate the GacS/GacA two-component system which in turn triggers transcription of the small regulatory RNAs RsmY and RsmZ. These sRNAs sequester multiple copies of the RNA-binding protein RsmA, antagonising its function. The RsmA/CsrA proteins act as translational repressors by binding to the GGA-motifs in the untranslated region of target mRNAs and blocking ribosome binding. In this study, the biological function of RsmN, an RsmA homologue with a conserved RNA-binding pocket but a distinct protein folding, the predicted autoregulatory mechanism of RsmN, the nature of target transcripts of RsmN, and the cross-regulation between the two Rsm proteins were investigated.